Multi-Participant Blinded Investigation into Internal Losses of Medication in Commercially Available Mixing Inlets: Testing Different Orally Inhaled Product Classes Following Pharmacopeial Methods - Andersson, Patrik U; Clay, Jim; Parry, Mark; Iley, Teresa; Roberts, Daryl L; Slator, Lois; Svensson, Mårten; Mohammed, Hlack; Mitchell, Jolyon P (Journal of aerosol medicine and pulmonary drug delivery, 2025)
The "Miller" design of mixing inlet (MI) enables a cascade impactor to operate at a constant flow rate while the orally inhaled product-on-test is evaluated at varying flow rates by controlling the flow of air via its side-arm. As part of the European Pharmaceutical Aerosol Group (EPAG) Impactor subgroup, we report a cross-industry experimental investigation by five organizations to determine internal losses of different inhaler-generated aerosolized medications within commercially available MIs, focusing on pharmacopeial methods for product testing. Evaluations were undertaken of solution and suspension formulations delivered by pressurized metered dose inhalers (pMDIs), passive dry powder inhalers (DPIs), and compressed air-jet and vibrating mesh nebulizers. Four different apparatuses were evaluated at different constant air flow rates entering the MI side arm. The nebulizers were tested utilizing a variable adult flow profile generated by a breathing simulator. Losses within the MI were generally <5%, expressed as a percentage of the delivered mass of active pharmaceutical ingredient (API) ex-inhaler. These losses were sufficiently small that they can in most cases be accommodated within the allowance of ±5% OIP label claim emitted mass/actuation in the pharmacopeial compendia for total internal losses for aerodynamic particle size distribution (APSD) determination. However, corresponding average losses were between 2.8% and 5.2% of the mass of API presented to the MI for the blister-based DPIs. APSD-derived measures were largely unaffected by the magnitude of pressurized air flow up to 60 L/min to the side-arm of the MI, except for the solution-formulated pMDI, where increasing flow rate was associated with reduced mass median aerodynamic diameter and increased geometric standard deviation, suggestive of a dependency related to ethanol co-solvent evaporation rate. MI loss evaluation should be considered an important part of method development to minimize internal losses of the aerosolized medication being sampled.